Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru - Siti Nurhidayatul Hasanah (Tarbiyah Departement collaboration with AMCA, 2016)
As an institution that has long been developing, the school is an institution that is complex and unique. Is complex because of the madrassa as an organization in which there are various dimensions to each other interrelated and mutually determine. While unique madrassa as an institution that has certain characteristics that are not owned by other organizations. Head madrasah professionals need to succeed in government programs are being rolled out as local autonomy, decentralization of education, school-based management, competency-based curriculum. All of it requires the participation and professional performance headmaster. The school principal professional new paradigm in the management of education will have a positive impact and a fairly fundamental change in the renewal of the education system in schools.